Ukraina a procesy przemian europejskich Przeszłość i teraźniejszość - Chodubski, Andrzej (Eastern Review, 2014)
Author put emphasis in the article on the following facts: 1. Ukraine suffered in the past from the constant wars, uprisings, political terror and various political intrigues; 2. It’s identity is ripped by cultural and civilizational cleavage and divided between West and East; 3. Cultural and civilizational cleavage opens the way to the rivalry between Russia and Western Europe; 4. Its historical development shows tendencies of integration and disintegration based on European values; 5. External observers, including Polish ones, are prone to perceive Ukraine as an area of cultural and civilizational backwardness, that stimulates many foreign actors to openly interfere with its internal affairs and impose Ukrainians alien patterns of cultural and civilizational activity.